2015
DOI: 10.1523/jneurosci.5010-14.2015
|View full text |Cite
|
Sign up to set email alerts
|

Altered Resting-State Functional Connectivity in Cortical Networks in Psychopathy

Abstract: Psychopathy is a personality disorder characterized by callous antisocial behavior and criminal recidivism. Here we examine whether psychopathy is associated with alterations in functional connectivity in three large-scale cortical networks. Using fMRI in 142 adult male prison inmates, we computed resting-state functional connectivity using seeds from the default mode network, frontoparietal network, and cingulo-opercular network. To determine the specificity of our findings to these cortical networks, we also… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

19
104
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 92 publications
(124 citation statements)
references
References 64 publications
19
104
1
Order By: Relevance
“…Our results further revealed that behavioral psychopathic traits related to heightened BLA connectivity with a frontoparietal cluster formation potentially relevant to psychopathy [Cohn et al, 2015; Glenn et al, 2009; Juarez et al, 2013; Philippi et al, 2015], which extended from the posterolateral parietal cortices to dorsolateral, ventrolateral, and rostromedial prefrontal territories. While these interconnected neocortical regions clearly serve myriad of functions, recent theories surmise their collective functioning reflective of a frontoparietal control system, which ostensibly supports executive control and behavioral inhibition in the context of goal‐directed behavior [Bressler and Menon, 2010; Luckmann et al, 2014; Menon, 2011; Seeley et al, 2007].…”
Section: Discussionsupporting
confidence: 58%
See 4 more Smart Citations
“…Our results further revealed that behavioral psychopathic traits related to heightened BLA connectivity with a frontoparietal cluster formation potentially relevant to psychopathy [Cohn et al, 2015; Glenn et al, 2009; Juarez et al, 2013; Philippi et al, 2015], which extended from the posterolateral parietal cortices to dorsolateral, ventrolateral, and rostromedial prefrontal territories. While these interconnected neocortical regions clearly serve myriad of functions, recent theories surmise their collective functioning reflective of a frontoparietal control system, which ostensibly supports executive control and behavioral inhibition in the context of goal‐directed behavior [Bressler and Menon, 2010; Luckmann et al, 2014; Menon, 2011; Seeley et al, 2007].…”
Section: Discussionsupporting
confidence: 58%
“…Interpersonal psychopathic traits additionally related to stronger CMA connectivity with a network of cortical midline structures growingly implicated in psychopathy [Anderson and Kiehl, 2012; Philippi et al, 2015; Pujol et al, 2012], which extended from the precuneal and posterior cingulate cortices to rostral and ventral portions of the medial prefrontal territory. Notwithstanding their myriad functions, these interconnected cortical regions seem to serve as key nodes within the so‐called default mode network (DMN), whose network function putatively supports internally and externally directed sociocognitive processes [Andrews‐Hanna et al, 2010; Li et al, 2014].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations